The Annapurna Water Cooperation Consensus - Gautam, Upendra (Hydro Nepal: Journal of Water, Energy and Environment, 2014)
Not Available. DOI: http://dx.doi.org/10.3126/hn.v15i0.11382 HYDRO Nepal Journal Journal of Water, Energy and Environment Volume: 15, 32014, July Page: 90-92